Analisis Pengembangan Pembelajaran Keterampilan Gerak Dasar Tendangan Pencak Silat - Rino Lusiyono Lucius; Zusyah Porja Daryanto (IKIP PGRI Pontianak, 2022)
The purpose of writing this literature review is: To find out the general description of pencak silat movement skills which includes analysis of basic movement skills, determination of training models to improve movement skills, and development of training models to improve pencak silat movement skills. The design in this analysis is a literature review with the PICOS approach, then analyzed using critical appraisal analysis to analyze from the core of the journal, the results of the study so as to find out the similarities and differences between these journals. The literature journal above shows varied results on pencak silat movement skills. The selection of the 3 journals was adjusted to the researcher's aim, namely to analyze the movement skills of pencak silat. Based on a literature review from 3 journals, it can be concluded that in order to improve the quality of pencak silat movement skills, an analysis of movement skills is needed then make a classification and map the results in a table. Determining the right training model is also needed to improve pencak silat movement skills. If this is not enough, the development of a model/exercise program is also highly recommended so that the expected results are truly optimal as expected.